The Correlation of Lovaas Method Application with The Obedient of Autism Child - Ah. Yusuf; Khoridatul Bahiyah; Laila Isna (Jurnal Ners, 2009)
Introduction : Autism is a behavioral dissorder which can be identified by three factors i.e.: communication, socialize and stereotyping. Lovaas method was a structural method, having a well-composed material which can be implemented one on one with very clear instructional steps. This study was aimed to explain the correlation of lovaas method implementation with the obedience in children with autism.Methods : This study used cross sectional  design involved 15 respondents for children with autism and 15 respondents of therapist who met inclusion criteria, taken by accidental sampling.  The independent variable was lovaas method and the dependent variable was the obedience. Data were collected by using observation and questionaire. Data were  analyzed using Gamma and Somers’d test with level of significance α ≤ 0.05.Results : Results showed that there was moderate correlation between lovaas method implementation with the obedience in children with autism (p = 0.026). Conclution: It can be concluded that lovaas method has correlation with the obedience in children with autism. Discussion : Lovaas method can shape obedience with reinforcement when children can respond order from therapist which is having more authority in giving rewards. For further studies the implementation of lovaas method should be intended to reveal other possible capacity in children with autism.